2018
DOI: 10.1002/jrs.5334
|View full text |Cite
|
Sign up to set email alerts
|

DFT calculations of the IR and Raman spectra of anthraquinone dyes and lakes

Abstract: The IR and Raman spectra of alizarin, purpurin, kermesic acid, and carminic acid have been computed performing density functional theory calculations at the B3LYP/6‐31G(d) level of theory. The computational approach adopted has been validated on the basis of a series of calculations with different level of theory on the anthraquinone molecule, the common moiety of these dyes. The computed vibrational frequencies have been adopted as a guideline to propose the vibrational assignment of the dyes and to obtain us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Additionally, by means of the density functional theory (DFT) calculations with the B3LYP hybrid theory level, the optimized geometry, wavenumber, and intensity of the vibrational bands of the investigated drug are provided. Such calculation method provides very good agreement between the calculated spectra and the corresponding experimental spectra of many molecules [10,[17][18][19][20]. Since there are a lot of publications regarding biological activity of erlotinib [21] and its successful application in NSCLC therapy [22,23], there are no reports describing the 3D structure of this drug in detail what determines its application.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Additionally, by means of the density functional theory (DFT) calculations with the B3LYP hybrid theory level, the optimized geometry, wavenumber, and intensity of the vibrational bands of the investigated drug are provided. Such calculation method provides very good agreement between the calculated spectra and the corresponding experimental spectra of many molecules [10,[17][18][19][20]. Since there are a lot of publications regarding biological activity of erlotinib [21] and its successful application in NSCLC therapy [22,23], there are no reports describing the 3D structure of this drug in detail what determines its application.…”
Section: Introductionmentioning
confidence: 80%
“…Bond length (Å) Bonds Angle (°) Bonds Dihedral angle (°) C 1 -C 2 1.204 C 2 -C 3 -C 8 119.5 C 6 -C 7 -N 9 -C 10 − 179.3 C 2 -C 3 1.430 C 8 -C 7 -N 9 124.5 N 9 -C 10 -C 11 -C 12 1.071 C 3 -C 4 1.403 N 9 -C 10 -N 19 120.0 C 11 -C 12 -C 13 -O 20 174.9 C 4 -C 5 1.390 N 9 -C 10 -C 11 118.8 C 16 -C 15 -C 14 -O 25 − 179.1 C 5 -C 6 1.388 C 10 -C 11 12 1.414 C 15 -C 14 -O 25 125.0 C 12 -C 13 1.374 C 14 -O 25 -C 26 118.9 C 13 -C 14 1.433 O 25 -C 26 -C 27 108.4 C 14 -C 15 1.378 C 26 -C 27 -O 28 109.4 C 15 -C 16 1.414 C 27 -O 28 -C 29 112.8 C 16 -N 17 1.367 N 17 -C 18 1.310 C 18 -N 19 1.351 N 19 -C 10 1.323 C 11 -C 16 1.418 C 13 -O 20 1.364 O 20 -C 21 1.441 C 21 -C 22 1.519 C 22 -O 23 1.418 O 23 -C 24 1.412 C 14 -O 25 1.356 O 25 -C 26 1.428 C 26 -C 27 1.511 C 27 -O 28 1.412 O 28 -C 29 1.414…”
Section: Bondmentioning
confidence: 99%
“…Hydrolysis of the pigment results in higher concentration of free dye molecules. In the SERS spectrum of the paint layer after HF hydrolysis, bands of alizarin (~345, 665, 1160, 1291 and 1325 cm −1 ) weak bands of purpurin (~968 (γ (CH)), 1068 (δ (OH) + δ (CH) [ 33 ] cm −1 ) and bands of carminic acid (shoulder at ~466 cm −1 , 1,447 and 1,574 cm −1 ) could be observed. A weak band at ~1588 cm −1 is also visible, and it could be assigned either to madder lake or cochineal lake pigment.…”
Section: Resultsmentioning
confidence: 99%
“…Pagliai and co‐workers carried out DFT calculations of the IR and Raman spectra of anthraquinone dyes and lakes. The computed vibrational frequencies have been adopted as a guideline to propose the vibrational assignment of the dyes and to obtain useful information on the Raman spectra of their aluminium complexes …”
Section: Art and Archaeologymentioning
confidence: 99%
“…The computed vibrational frequencies have been adopted as a guideline to propose the vibrational assignment of the dyes and to obtain useful information on the Raman spectra of their aluminium complexes. [136] 14.4 | Geological, archeological, and extraterrestial related samples Montagnac et al reported Spark plasma sintering preparation of reference targets for Raman and other spectroscopy instruments involved in Mars and future space missions and more generally in-field work. [137] Wojcieszak used Raman microspectroscopy to analyze material processed with 58,000-year-old grindstones from Sibudu (KwaZulu-Natal, South Africa).…”
Section: Time-resolved and Ultrafast Raman Spectroscopymentioning
confidence: 99%